THE BEST FRAMEWORK FOR QA AUTOMATION TESTING:ADVANTAGES AND DISADVANTAGES OF ROBOT FRAMEWORK - Shaikenov, Temirlan; Zhanysbek, Ulbike; Turganbekov, Shynggyskhan (Journal of Emerging Technologies and Computing, 2024)
Nowadays quality assurance automation testing has a lot of frameworks which help to develop quality automation test cases. Currently most developers or manual testers want to start develop automation test cases and they do not know which the best framework to learn. We are interesting to focus in one framework and find all advantages and disadvantages of this framework.This paper contains all full information about Robot framework in testenvironment. Seven criteria’s help to find positive and negative sides of thisframework. With using Robot framework in automation test case we canimprove all manual tests.